When the Cat's Away : The Effects of Spousal Migration on Investments on Children - Lucia, Rizzica (World Bank, Washington, DC, 2016)
Household expenditures for children-related goods may change when one of the parent migrates and do so differently depending on whether it is the mother or the father that leaves. A sequential model that explains migration and budget allocation choices is proposed and its predictions are tested on data from Indonesia. Selection of households into female migration is accounted for using a set of instrumental variables derived from the model. Results show that when children are left with fathers, the household budget is significantly diverted toward the purchase of adult private goods, but the share of budget devoted to children remains unaffected because mothers compensate by giving up their own private consumption and sending home more remittances.